2020
DOI: 10.1186/s12937-020-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flaxseed supplementation on metabolic status in women with polycystic ovary syndrome: a randomized open-labeled controlled clinical trial

Abstract: Background: Polycystic Ovary Syndrome (PCOS) is known as the most common endocrine disorder of women in reproductive ages. With the increasing prevalence of PCOS in different countries, the use of herbal medicine as an alternative treatment is growing in these patients. This study aimed to evaluate the effects of flaxseed powder supplementation on metabolic biomarkers of patients with PCOS. Methods: This randomized open-labeled controlled clinical trial was conducted on 41 patients with PCOS. The participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…PCOS is known to be a common cause of anovulatory infertility; however, the mechanisms of anovulation endure not known 3 . Based on Rotterdam criteria, PCOS was diagnosed by confirming clinical features of three out of two; (i) oligo-anovulation, (ii) hyperandrogenism and (iii) appearance of polycystic ovaries in ultrasound [4]. Every 16-20% of reproductive women are facing both infertility and menstrual problems 5 .…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is known to be a common cause of anovulatory infertility; however, the mechanisms of anovulation endure not known 3 . Based on Rotterdam criteria, PCOS was diagnosed by confirming clinical features of three out of two; (i) oligo-anovulation, (ii) hyperandrogenism and (iii) appearance of polycystic ovaries in ultrasound [4]. Every 16-20% of reproductive women are facing both infertility and menstrual problems 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Linseed exerts a positive effect on adiponectin expression because it contains alpha-linolenic acid (ALA), which may also act as a ligand for the PPARγ receptor. Haidari et al [ 55 ] conducted a randomized study in a group of women with PCOS. They demonstrated that linseed might significantly increase adiponectin concentrations.…”
Section: Diet-related Factors With a Positive Influence On Adiponectin Concentrationsmentioning
confidence: 99%
“…A recently published clinical trial recruited 41 women suffering with polycystic ovary syndrome, randomly segregated into two groups, group 1 subjected to lifestyle changes (American Heart Association recommendations + >30 min moderate to intense activity 3x/week) plus 30 g/day brown flaxseed flour in salad, yogurt or cold drinks, and group 2 subjected to the same lifestyle changes only, for 12 weeks [ 70 ]. The authors found that the flaxseed group showed significant improvements in insulin, homeostasis model assessment of insulin resistance (HOMA-IR), TG, hs-CRP, IL-6, leptin, HDL-C and adiponectin, as compared to the non-flaxseed group [ 70 ].…”
Section: Alternative Plant Sources Of N3-pufasmentioning
confidence: 99%